Mental health amidst multiple crises: trends and sociodemographic risk factors in Austria’s general population - Humer, Elke; Pieh, Christoph; Probst, Thomas; Dinhof, Carina; Schaffler, Yvonne; Zeldovich, Marina (Frontiers in Psychiatry, 2025)
BackgroundIn recent years, mental health in Austria has faced substantial challenges due to a series of both global and regional crises.ObjectiveThis study aimed to assess changes in mental health indicators within the Austrian population over time from April 2022 to October 2024 and to identify sociodemographic correlates of poor mental health.MethodsTwo cross-sectional online surveys on representative samples of the Austrian general population were conducted at two timepoints: April 2022 (n = 1,032) and October 2024 (n = 2,025). Mental health indicators, including depression, anxiety, insomnia, alcohol misuse, and stress, were measured using validated scales. Sociodemographic data were collected to examine associations with mental health indicators. Chi-squared tests and t-tests were conducted to compare mental health indicators between 2022 and 2024, and multivariable logistic regression models were applied to examine associations with sociodemographic data.ResultsClinically relevant symptoms of depression and high stress decreased from 2022 to 2024 (depression from 28.3% to 21.6%, stress from 56.3% to 51.0%; p < 0.01), while other symptoms remained stable. Sociodemographic analysis revealed that female gender, younger age, lower income, unemployment, migration background and lack of partnership were associated with higher odds for several mental health issues.ConclusionsFindings suggest small improvements in mental health from 2022 to 2024 and identified sociodemographic risk factors linked to mental health vulnerabilities.